2020
DOI: 10.3390/min10060502
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Microstructure of Filtration Materials on Its Auto-Activation for Manganese Removal from Groundwater

Abstract: The study investigates the impact of pore structure parameters of three chemically non-active filtration materials on the auto-activation time and the height of the filtration zone for manganese removal from groundwater. At a technical scale, the activation is a long process which may require a period of up to three months. The process can be shortened by the use of porous filtration materials. In this study, three filtration materials (silica sand, chalcedonite sand, GAC—granulated activated carbon) were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…With the deepening of research, it has been found that the nature of the decrease in mechanical properties of freezing-thawing porous materials is that the freezing-thawing action changes their internal microstructure [25][26][27][28][29][30][31][32][33][34]. Tang, LY [35] used nuclear magnetic resonance (NMR) to analyze the effect of freeze-thaw cycles on the internal pore structure of the soil-rock mixture.…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of research, it has been found that the nature of the decrease in mechanical properties of freezing-thawing porous materials is that the freezing-thawing action changes their internal microstructure [25][26][27][28][29][30][31][32][33][34]. Tang, LY [35] used nuclear magnetic resonance (NMR) to analyze the effect of freeze-thaw cycles on the internal pore structure of the soil-rock mixture.…”
Section: Introductionmentioning
confidence: 99%